Effects of Standardized Ileal Digestible Tryptophan:Lysine Ratio on Growth and Carcass Performance of Finishing Pigs Fed Ractopamine HCl - H. E. Williams; M. D. Tokach; S. S. Dritz; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband; J. A. Soto (Kansas Agricultural Experiment Station Research Reports, 2020)
Recent research has reported that increasing standardized ileal digestible (SID) Trp:Lys ratio above 20% in finishing pigs fed ractopamine HCl (RAC) resulted in improved growth and carcass performance, however, this response has been inconsistent. Therefore, the objective of this study was to evaluate the effects of feeding high SID Trp:Lys ratios with RAC on growth and carcass performance. A total of 1,791 finishing pigs (PIC 1050 × 337, initially 245.1 lb BW) were used in a 27-d study to evaluate the effects of feeding high SID Trp:Lys ratios on growth and carcass performance of pigs fed ractopamine HCl (RAC, Paylean, Elanco Animal Health, Greenfield, IN). Pens of 25 or 26 pigs were allotted by initial body weight (BW) and randomly assigned to 1 of 5 dietary treatments with 14 replications per treatment. The dietary treatments included 5 SID Trp:Lys ratios (20, 22, 24, 26, and 28% of Lys). All diets were formulated to 0.90% SID Lys and contained 10 ppm ractopamine. At d 27, pigs were transported to a commercial packing plant (JBS Swift and Company, Worthington, MN) for processing and carcass data collection. For overall growth performance, increasing SID Trp:Lys ratio increased (linear;P=<0.0001) SID Trp intake and Trp g/kg of gain; however, there was no evidence of a treatment difference (P>0.10) for average daily gain (ADG) or feed efficiency (F/G). For carcass characteristics, increasing SID Trp:Lys decreased (linear;P= 0.002) carcass yield and tended to decrease (P =0.078) lean percentage. There was no evidence of treatment differences (P>0.10) for hot carcass weight, loin depth, carcass ADG, or carcass feed efficiency. The results from this study showed that grams per day of SID Trp intake ranged from 5.5 to 7.5. Greater feed intakes observed in this study resulted in increased Trp g/d of intake and could potentially be a reason why no evidence for treatment differences was observed. In summary, increasing SID Trp:Lys ratios above 20% (approximately 5.4 g SID Trp intake per day) in pigs fed RAC did not improve growth or carcass performance.
Keywords: amino acid; growth; finishing pigs; tryptophan